A New self-expandable transcatheter aortic valve for transapical implantation: feasibility in acute and chronic animal experiments. (June 2013) - Wendt, Daniel; Pasa, Susanne; Kahlert, Philipp; Delaloye, Stéphane; Al-Rashid, Fadi; Price, Vivien; Jánosi, Rolf-Alexander; Borenstein, Nicolas; Behr, Luc; Konorza, Thomas; Erbel, Raimund; Jakob, Heinz; et al.
Abstract Objectives. Transcatheter aortic valve implantation (TAVI) is currently expanding worldwide, however all available prostheses share some fundamental design drawbacks. We investigated the feasibility, safety and hemodynamic performance of the innovative transapical Acurate TA™ self-expandable device, which has the unique advantage of offering anatomically correct self-alignment within the aortic root. Design. Transapical TAVI was performed in six acute swine and six chronic sheep procedures, with follow-up of 7, 14, 21, 28, 60 and 90 days. TAVI was performed under TEE and angiographic guidance without rapid pacing. Results. A partial sternotomy approach was used to access the LV-apex. All valve implantations were performed as planned and all animals survived the implantation procedure. After deployment, no migration, embolization or coronary obstruction was observed during the observation period. Intraoperative TEE examination identified no signs of intravalvular leakage or valve dysfunction. Transvalvular mean pressure gradients were 5.4 ± 2.2 mmHg decreasing during follow-up (1.6 ± 0.8 mmHg, 1.8 ± 0.8 mmHg, 1.3 ± 0.2, 1.8 ± 0.7 mmHg, 1.6 ± 0.8 mmHg), with a slight increase atday 90 (4.0 ± 2.4 mmHg, P < 0.05). Macroscopic examination at necropsy showed correct anatomical positioning of the valve stent without any signs of structural valve deterioration. Conclusions. These first results of the innovative self-expandable transapical ACURATE TA™ device explore the feasibility and safety of anatomically correct off-pump implantation with optimal hemodynamic results.